La construction professionnelle par la quête d’un langage commun, le cas des enseignants débutants en classe maternelle - Amélie Alletru (Recherches en Éducation)
This article presents a metaphorical interpretation of efforts provided by novices in building up the gestures necessary for their job. Attempting to integrate a professional community, beginners have no choice, in the course of their first work experiences, but to learn its codes, its relations between subject, matter of work and other actors, in a system of interactions they discover from the inside: they are in search of a “common language” within that universe. Based on a study carried out with trainee primary teachers at the time of their first practice in nursery classes, the articulation of professional didactics, activity clinic and “course of action” frameworks allows one to consider characteristic features of that learning of a “common language”, whose mastery then means actual professionalism.